Audit Committee Characteristics and Sustainable Growth Among Selected Listed Non-Financial Firms in Nigeria - Taiwo Asaolu; Johnson Olowookere; Aderemi Adebayo; Tajudeen Kareem (Iranian Journal of Accounting, Auditing & Finance, 2022)
Sustainable growth involves a situation where growth is witnessed with no increase in assets, equity issuance and liabilities. An effective corporate governance mechanism, especially the audit committee, is needed to achieve an optimum sustainable growth rate. The influence of audit committee characteristics on the manufacturing firms’ sustainable growth during the financial crisis cannot be overemphasized. Hence, this study was carried out to investigate the influence of audit committee characteristics on the sustainable growth rate of non-financial firms in Nigeria. The study population was listed as manufacturing companies on the Nigerian Stock Exchange (NSE). A sample size of 60 manufacturing firms was selected using a purposive sampling technique and content analysis, covering ten financial years (2011 to 2020). The results showed that audit committee size, audit committee independence and audit committee financial expertise were positively and significantly associated with sustainable growth rate. The study was anchored on agency theory because it showed that effective audit committee characteristics greatly contributed to the overall companies’ goal congruence. From the foregoing, the study recommended that an audit committee should be large, with a great sense of independence and professionalism to make non-financial companies attain sustainable growth.